1998
DOI: 10.1093/ije/27.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of selected foods and beverages and the incidence of gastric cancer among the Japanese residents of Hawaii: a prospective study

Abstract: Background We report on the associations between the intake of certain foods and beverages and the incidence of gastric cancer in a cohort of 11 907 randomly selected Japanese residents of Hawaii (6297 women and 5610 men). MethodsThe daily intake of six beverages, cigarettes and alcohol and the weekly frequency of intake of 13 foods and food groups was estimated with a short food frequency questionniare. Over an average follow-up period of 14.8 years, 108 cases of gastric cancer (44 women, 64 men) were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
151
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(162 citation statements)
references
References 54 publications
7
151
4
Order By: Relevance
“…The few cohort studies that reported results on salt and stomach cancer risk found no clear associations [48][49][50][51][52][53]. Contrary to our finding that dietary salt intake was associated with an increased stomach cancer risk, the only cohort study that reported on sodium intake found no difference in mean daily sodium intake between cases and non-cases [48].…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…The few cohort studies that reported results on salt and stomach cancer risk found no clear associations [48][49][50][51][52][53]. Contrary to our finding that dietary salt intake was associated with an increased stomach cancer risk, the only cohort study that reported on sodium intake found no difference in mean daily sodium intake between cases and non-cases [48].…”
Section: Discussioncontrasting
confidence: 98%
“…Two cohort studies reported a significantly increased risk for consumption of broiled fish (RR ¼ 1.7) [52] and salted fish (RR ¼ 2.0) [50]. The other three cohort studies found no association between stomach cancer incidence and the individual or total intake of several types of high-salted foods [49,51,53]. It is possible that the increased risks could be attributed to other compounds of the foods (possible carcinogens) developed during the preservation process, but not to salt content of the foods [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies, consumption of food rich in nitrate and nitrite, smoked food, a high salt diet and a 4 A kind of kimchi prepared with salted radish and the same subingredients as Baiechu kimchi.- 5 A kind of kimchi prepared with radish and a large quantity of salt water.-*p Ͻ 0.05; **p Ͻ 0.01. high starch diet have seemed to be risk factors for GC, whereas high consumption of fresh fruits and vegetables, milk and milk products have seemed to be protective. [5][6][7][8][9][10][11][12][13][14][15] Although controversial, it has been reported that dietary fat, meats, fish, seasonings and beverages such as coffee and tea are also associated with increased risk of GC. 6,10,11,15,24 Intake of charcoal grilled beef significantly increased the risk of GC in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the relationship between diet and GC have suggested that foods rich in nitrate or nitrite, a high salt diet, smoked meat or fish and a high carbohydrate diet increase the risk of GC, whereas high consumption of fresh vegetables, fruits and dairy products decreases the risk of GC, although the findings are not always consistent. [5][6][7][8][9][10][11][12][13][14][15] Dietary habits of Korean people can be characterized as a high intake of salty foods and carbohydrates and a higher intake of cooked rather than fresh vegetables. For this reason, it is necessary to investigate the effect of dietary factors on GC in Korea.…”
mentioning
confidence: 99%